COMPETITIVE ANALYSES OF LOCAL BAKERIES IN PRISHTINA/ REPUBLIC OF KOSOVO - Fejza, Ejup; Ismajli, Ali; Misini, Shkumbin (European Scientific Journal, ESJ, 2013)
The main problem of today’s companies is the division between marketing and sales as separate departments in company, or better saying, including the sales as division within the marketing department. Through this “regulation” of departments, enterprises will have more knowledge about market and competition and will be a step forward their competitors. The main purpose of this paper is to identify competitive analyses of local bakeries in the Capital City of Kosovo, Prishtina, and define how they act toward the competition and what strategies they use to compete in a very competitive business environment, pricing or quality based products offered to customers. While doing a research and analyzing competition and competitive strategies of bakeries, I found out that most of bakeries are based on achieving their competitive advantage in the market through lower prices than competitor and few of them based its strategy toward offering qualitative products and services to the customers and through it they have a better image and got customer loyalty. This situation is as a result of not having marketing department in any bakery or a person who is responsible for marketing. The only reason for not having established marketing was that these companies need more time to transition from sales to marketing activities. The data for research were collected through questionnaire in fifteen bakeries within the Prishtina city. Methods used for research have been descriptive, comparative, analysis, and synthesis. The research instrument was a questionnaire, the technique has been direct communication and research was conducted between months February and March 2012.